The Use of Financial Analysis in Calculating the Taxable Income of Companies in Jordan and Palestine: An Applied Study on Local Telecommunications Companies in Jordan and Palestine 2023 - Qutait, Zaid (The Arab Journal of Administration, 2023)
The study aims to provide a new ways for the tax estimator to rely on realistic, tangible information to determine the income tax in a scientific and far approach, which is represented by using ratio analysis instead of an estimate that depends on the vision and knowledge of the tax estimator, which may be limited to the taxpayer. The study also aims to work to reduce the gap between the taxpayers and the income tax departments and give confidence to the taxpayers to disclose their real financial data and the proportionality of the tax with the actual work size of the taxpayers and increase the tax commitment and voluntary disclosure of activities and financial statements and their agreement to the ground and the status of the actual taxpayer. An analytical study was conducted of the financial statements of the local telecommunications companies in Jordan and Palestine: they are among the largest and leading companies in the Palestinian and Jordanian markets. The study main conclusion was that when relying on financial analysis tools (financial ratios) by the tax estimator helps to identify the extent of the company’s ability to achieve profits, and this helps in determining the amount of tax by reaching a real estimate or very close to the real taxable income. The study concluded several recommendations, the most prominent of which was the need to use scientific methods in estimating taxable income instead of the traditional methods adopted at the present time in the income tax, and by this use it reduces the gap between it and the taxpayers.